Finding Protocol Manipulation Attacks - Millstein, Todd; Govindan, Ramesh; Musuvathi, Madan; Kothari, Nupur; Mahajan, Ratul (ACM SIGCOMM, 2011)
We develop a method to help discover manipulation attacks in protocol implementations. In these attacks, adversaries induce honest nodes to exhibit undesirable behaviors by misrepresenting their intent or network conditions. Our method is based on a novel combination of static analysis with symbolic execution and dynamic analysis with concrete execution. The former finds code paths that are likely vulnerable, and the latter emulates adversarial actions that lead to effective attacks. Our method is precise (i.e., no false positives) and we show that it scales to complex protocol implementations. We apply it to four diverse protocols, including TCP, the 802.11 MAC, ECN, and SCTP, and show that it is able to find all manipulation attacks that have been previously reported for these protocols. We also find a previously unreported attack for SCTP. This attack is a variant of a TCP attack but must be mounted differently in SCTP because of subtle semantic differences between the two protocols.